INTEGRATION OF ESG PRINCIPLES IN RISK ASSESMENT OF ISLAMIC FINANCIAL PRODUCTS: A MAQASID SHARIAH-BASED APPROACH - Tulus Pujo Nugroho (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to develop a risk assessment framework for Islamic financial products by integrating Environmental, Social, and Governance (ESG) principles with maqashid shariah. ESG has become a global standard for evaluating investment sustainability; however, its adoption in the Islamic finance context remains limited and unstructured. Using a qualitative exploratory approach and systematic literature review, the study identifies ESG indicators that align with the objectives of maqashid shariah and formulates a value-based conceptual risk assessment model. The findings indicate a strong synergy between ESG indicators and maqashid shariah, revealing significant opportunities for Islamic financial institutions to adopt this model in order to strengthen public trust and enhance global competitiveness.